The Contribution of the Architect Pascuala Campos to the Implementation of a Gender Perspective in the Galician Context - Ainoa Fernández Cruces; Goreti Sousa; Paulo Guerreiro; Mariana Correia (Arts, 2020)
The incorporation of women in society, as active professionals, was probably one of the most important parameters of modernity in the last century. Until the beginning of the twentieth century, women who entered the world of architecture were, generally, assigned to the design of domestic interiors. Thus, they were always in the background, which contributed to the concealment of the female gender perspective in architecture and an incomplete vision of its history. The general purpose of this article is to address the implicit problematic of the female contribution to architecture, through a theoretical reflection that aims at recognizing the relevant impact of Pascuala Campos’s work to the discipline in Galicia, Spain. The Spanish social and architectonic contexts, as well as the biography of Pascuala Campos, are analyzed to better understand her theoretical and architectonic production. The analysis combines data from different sources, mainly documental research, interviews, and architectonic surveys. The basic principles stressed in the theoretical production of Pascuala Campos are thus identified and served as analytic categories for the survey of the Combarro Urban Intervention. These results allowed the identification of concepts and projected guidelines interpreted as gender perspective-oriented.